On shift radix systems over imaginary quadratic euclidean domains - Pethő Attila; Varga Péter; Weitzer Mario (2015)
In this paper we generalize the shift radix systems to finite dimensional Hermitian vector spaces. Here the integer lattice is replaced by the direct sum of imaginary quadratic Euclidean domains. We prove in two cases that the set of one dimensional Euclidean shift radix systems with finiteness property is contained in a circle of radius 0.99 around the origin. Thus their structure is much simpler than the structure of analogous sets.
Keywords: Természettudományok; Matematika; Számítás- és információtudomány